2014
DOI: 10.1111/fcp.12085
|View full text |Cite
|
Sign up to set email alerts
|

N‐feruloylserotonin in preventive combination therapy with methotrexate reduced inflammation in adjuvant arthritis

Abstract: Many of disease-modifying anti-rheumatic drugs often have side effects at high doses and/or during long-term administration. Increased efficacy without increased toxicity is expected for combination therapy of rheumatoid arthritis (RA). The aim of the study was to examine the effect of N-feruloylserotonin (N-f-5HT) and methotrexate (MTX) in monotherapy and in combination therapy on disease progression and inflammation in arthritic rats. Adjuvant arthritis was induced by intradermal injection of Mycobacterium b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 45 publications
(53 reference statements)
5
21
0
Order By: Relevance
“…Previous studies suggest that production of proinflammatory cytokines such as TNF‐α, IL‐6, and IL‐β plays an important role in inflammatory responses (Kuncirova et al, ). To further investigate the underlying antiinflammatory mechanisms induced by the combination of MTX and TPE‐CA, we measured content of inflammatory cytokines such as TNF‐α, IL‐6, IL‐1β, and CRP as a systematic inflammatory marker (Christian Gytz et al, ) involved in RA rats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies suggest that production of proinflammatory cytokines such as TNF‐α, IL‐6, and IL‐β plays an important role in inflammatory responses (Kuncirova et al, ). To further investigate the underlying antiinflammatory mechanisms induced by the combination of MTX and TPE‐CA, we measured content of inflammatory cytokines such as TNF‐α, IL‐6, IL‐1β, and CRP as a systematic inflammatory marker (Christian Gytz et al, ) involved in RA rats.…”
Section: Resultsmentioning
confidence: 99%
“…After combination treatment with MTX and TPE‐CA, the number of PLT in CIA rats was markedly decreased. Chronic inflammation‐stimulated bone destruction is a characteristic pathological feature of RA (Kuncirova et al, ). Micro‐CT images showed that bone parameters, including BV/TV and Tb.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Matrix metalloproteinases (MMPs) are a family of latent zinc‐ and calcium‐dependent proteolytic enzymes that mediate changes in the extracellular matrix (ECM) participating in many physiological processes such as morphogenesis, development and apoptosis . Moreover, their role is crucial in various pathological processes as well, involved in the pathogenesis of different diseases such as chronic obstructive pulmonary disease , cancer , liver cirrhosis and arthritis , while they are also engaged in cardiovascular diseases including arterial hypertension , pulmonary hypertension , coronary artery disease , stroke and cardiac hypertrophy . They are gaining increasing clinical interest as important players in vascular remodeling, atherogenesis and thrombosis .…”
Section: Introductionmentioning
confidence: 99%